Carbocatalytic Cascade Synthesis of Polysubstituted Quinolines from Aldehydes and 2‐Vinyl Anilines. Issue 15 (16th July 2021) - Mäkelä, Mikko K.; Bulatov, Evgeny; Malinen, Kiia; Talvitie, Juulia; Nieger, Martin; Melchionna, Michele; Lenarda, Anna; Hu, Tao; Wirtanen, Tom; Helaja, Juho
Abstract: Oxidized active carbon (oAC) catalyses the formation of polysubstituted quinolines from o ‐vinyl anilines and aldehydes. The reaction proceeds in a cascade manner through condensation, electrocyclization and dehydrogenation, and gives access to a wide range of quinolines with alkyl and/or aryl substituents as demonstrated with 40 examples. The metal‐free catalytic procedure allows a heterogeneous protocol for the synthesis of various polysubstituted quinolines. The mechanistic studies imply that both the acid and quinoidic groups in oAC are integral for the catalytic manifold. Abstract :